2018
DOI: 10.15314/tsed.339522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the prolonged competitive season on semi-elite female volleyball players’ physical performance

Abstract: Despite the literature on the changes in the physical performance characteristics of elite female athletes during the competition period, up to this date, there was no study of the physical performances of both the aerobic and anaerobic contented of the semi-elite female volleyball players over the competitive season. For this reason, this study was carried out in order to determine the effect of prolonged competitive season on semi-elite female volleyball players' physical performance. Volunteer 47 athletes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The present study resulted in a significant improvement in both COD (1.6%) and 20m sprint performance (3.4%) of female volleyball players in the regional competitive season. These results were in line with the previous study in which Karahan (2018) reported that semi-elite female volleyball players' COD (1.6%) and sprint (2.1%) performances improved significantly during the long-term competition season. The present study also indicated that the improvement in linear sprinting (first period=2.4%, second period= 0.9%) and COD (first period= 0.7%, second period= 0.98%) abilities in the first period of the competitive season was significantly better than in the second period.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study resulted in a significant improvement in both COD (1.6%) and 20m sprint performance (3.4%) of female volleyball players in the regional competitive season. These results were in line with the previous study in which Karahan (2018) reported that semi-elite female volleyball players' COD (1.6%) and sprint (2.1%) performances improved significantly during the long-term competition season. The present study also indicated that the improvement in linear sprinting (first period=2.4%, second period= 0.9%) and COD (first period= 0.7%, second period= 0.98%) abilities in the first period of the competitive season was significantly better than in the second period.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, increased match load and prolonged rallies can induce significant degradation in the physical performance characteristics of the players by increasing both physiological and psychological stresses that trigger fatigue (Haneishi et al, 2007). Despite the specific measures taken, there may be significant fluctuations in physical performance variables during the competition season depending on many factors such as the fitness level of the athletes, intensity of the competitions, training volume or content (Karahan, 2018;Koutedakis, 1995). A limited number of studies provide data that seasonal variations in the physical performance characteristics of female volleyball players competing in different playing level (Hakkinen, 1993;Karahan, 2018;Nesser and Demchak, 2007; Rousanoglou, Barzouka and Boudolos 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations